The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-204x2012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética molecular de progênies de dendezeiro

Abstract: Resumo -O objetivo deste trabalho foi avaliar a diversidade genética, entre e dentro de progênies de dendezeiro tipo dura, de origem Deli. A caracterização genética foi feita com uso de marcadores microssatélites em 24 progênies usadas na produção comercial de sementes, sendo 22 provenientes de autofecundação e duas de cruzamentos entre irmãos completos. Foi realizada análise de variância molecular entre e dentro das progênies, com posterior construção de um dendrograma. Observou-se baixa variabilidade genétic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…The AMOVA results showed that 14% of variance occurred among offspring and 86% occurred within offspring ( Table 2). These results corroborate the expected variance in allogamous species, where crossing occurring naturally between parents and the variation within offspring are low (Glémin et al, 2006;Ferreira et al, 2012). Glémin et al (2006) showed that among various life history traits, mating systems have the greatest influence on patterns of polymorphism.…”
Section: Molecular Markers and Genetic Diversitysupporting
confidence: 84%
“…The AMOVA results showed that 14% of variance occurred among offspring and 86% occurred within offspring ( Table 2). These results corroborate the expected variance in allogamous species, where crossing occurring naturally between parents and the variation within offspring are low (Glémin et al, 2006;Ferreira et al, 2012). Glémin et al (2006) showed that among various life history traits, mating systems have the greatest influence on patterns of polymorphism.…”
Section: Molecular Markers and Genetic Diversitysupporting
confidence: 84%
“…The analysis also showed that 42.84 % of the genetic variation was found among individuals within families. This shows that the species is preferably cross-fertilized, since allogamous species retain much of their genetic variability distributed within their families, in contrast to self-pollinating species, where most of the genetic variability is between provenances (Ferreira et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Identifying genetically superior progenies that may be recommended for use in seed production would be an important step for improving the crop in Brazil (Valente et al 2017a). However, previous studies are necessary to provide a basis for strategies to make the best of the available genetic resources and to maintain a broad genetic base within breeding programs (Ferreira et al 2012). Genetic markers are a highly efficient tool for investigating the variability between and within progenies.…”
Section: Abstract Resumomentioning
confidence: 99%
See 1 more Smart Citation
“…Its economic prominence is due to its oil, being one of the world's leading sources of vegetable oil. (FERREIRA et al, 2012;USDA, 2012). E. guineensis oil can be extracted from both the fruit (palm oil) and the nut (palm kernel oil).…”
Section: Introductionmentioning
confidence: 99%